Peran Kantor Badan Pertanahan Nasional Kota Bandar Lampung Dalam Mengatasi Kepemilikan Tanah Absentee - Karmuz Karmuz; Fathur Rachman; Yuli Purwanti (VIVA THEMIS, 2018)
The ground is important for the community resources, good as a medium growing plants, and as a space or container place performs various functions. Land in relation to the issue, the government issued the law number 5 1960 re basic provisions concerning the fundamentals of agrarian affairs (UUPA). Next, as a form of uupa to this is that the , the government issued the act of number 56 prp 1960 on the provision of it a bit and government regulation no 224 1961 on the implementation of the subdivision of land and the provision of compensation, in article 3 paragraph (1) PP no. 1 224 1961 jo article 1 PP no. 1 41 years 1964 arranged the prohibition of land as guntai /absentee ownership. Highlights the difficulty in this research is what factors causing the occurrence of ownership of land as absentee in the city of bandar lampung and the role of national land agency bpn make glad the city of bandar lampung in overcome or solve the problems of their lands were absent.The kind of research used in this research is research descriptive namely research that seeks, described a symptom the, the incident happened when now to focus on actual problems as they are at the time of the visit.Approach that is used is the methodology of juridical law sosiologis.proses collection of data consists of the study of literature and field study. Next, the method of analysis in a qualitative analysis. The result showed that the cause of the absentee land ownership is the lack of legal awareness, community cultural factors, the law enforcement officials, the infrastructure and economic factors.The role of the national land agency to address the absentee land ownership in the city of bandar lampung by controlling the administration and control, law and to prevent new absentee land ownership of land agency kordinasi badly needed by the related agencies and, district the village head and PPAT / notary.